TRENDS OF HUMANE LITERACY IN EFL ASSESSMENT AS AN ALTERNATIVE FOR FUTURE LEARNING: A Systematic Review Paper - Syafika, Nurul; Inayatillah, Shilvy; Sulistyaningrum, Siti Drivoka (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This research is a systematic literature review that intends to investigate the future trends of humane literacy assessment for future learning by analyzing data obtained from Google Scholar and Google Trends which the publication discovered in the database is included as the data of this study. In total, 23 relevant publications from Google Scholar have been identified. Based on the findings. This study investigates the trend of incorporating humane literacy in English assessment practices as a proactive approach in future learning models and realizing the importance of cultivating sympathetic understanding, critical thinking, and moral awareness as well as language proficiency. By illustrating the trends and implications of sympathetic proficiency in EFL assessment, this study contributes to the ongoing conversation about the holistic development of language learners and offers insights for shaping future directions in language education and assessment practices.